2006
DOI: 10.1002/jccs.200600139
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Studies of Nickel ions Onto Sawdust of Dalbergia Sissoo

Abstract: Sawdust of Dalbergia sissoo, a byproduct of sawmills, was found to be a promising adsorbent for the removal of nickel ions from aqueous solution. Sorption of nickel ions onto sawdust of Dalbergia sissoo was studied using the batch technique. Kinetics studies show that nickel ions sorption process obeys a first order rate law. The applicability of the Langmuir and Freundlich models for the data was tested. Both the models adequately describe the experimental data of the biosorption of nickel ions. The sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Phanerochaete chrysosporium exhibited high efficiency in metal biosorption during the first 15 min of incubation time . Sawdust biomass recorded the maximum removal of Ni 2+ ions within 5 min . In the present study, BM1 and BM2 achieved the maximum removal after 30 min (97.32 and 98.3%, respectively) while for BM3, the maximum removal was noted after 60 min where 95.31% of Ni 2+ ions were removed.…”
Section: Discussionsupporting
confidence: 44%
“…Phanerochaete chrysosporium exhibited high efficiency in metal biosorption during the first 15 min of incubation time . Sawdust biomass recorded the maximum removal of Ni 2+ ions within 5 min . In the present study, BM1 and BM2 achieved the maximum removal after 30 min (97.32 and 98.3%, respectively) while for BM3, the maximum removal was noted after 60 min where 95.31% of Ni 2+ ions were removed.…”
Section: Discussionsupporting
confidence: 44%
“…Optimal pH of 2 to 5 has been reported by Khan et al (2004), Shukla et al (2005), and Igwe and Abia (2007). On the other hand, Habib-ur-Rehman et al (2006) and AbdelGhani et al (2007) reported an optimal pH of 6 to 6.5. Although, this study was carried out in the natural aquatic environment, the pH (6.61±0.07 -6.66±0.04) is slightly outside the reported value in the in vitro studies and may be responsible for the relative low adsorptive capacity of the sawdust in this study.…”
Section: Resultsmentioning
confidence: 97%
“…Several researchers have reported on varied dependence of pH in the removal of metal ions by sawdust and other agricultural wastes (Khan et al, 2004;Shukla et al, 2005;Habib-ur-Rehman et al, 2006;Hashem, 2007;Igwe and Abia, 2007;Abdel-Ghani et al, 2007). Optimal pH of 2 to 5 has been reported by Khan et al (2004), Shukla et al (2005), and Igwe and Abia (2007).…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were reported by Ceribasi and Yetis (2001) who stated that that the biosorption process was very rapid during the first 15 min of contact time. Habib-ur-Ruhman et al (2006) revealed that the biosorption process is rapid in the initial 5 min, and further increase in contact time up to 20 min had a marginal positive effect on this process. In comparison with the sample control it was found that the natural degradation increased with time to reach 6.8% after 90 min, the removal process with the bacterial biomass cells is much better than the control, it has the ability to remove 76.85% and 49.07% by the living and dead cells within short time (10 min) which might be related to the nature of biosorption as a fast reaction process.…”
Section: Factors Affecting Biosorption Processmentioning
confidence: 97%